Feeding preferences of Tripneustes gratilla Linnaeus Echinodermata Echinodea and the prospect for sea urchin aquaculture in South Africa - Scholtz, Rheinhardt (Department of Biological Sciences, 2017)
Sea urchin aquaculture for human food is a major industry, and there are prospects for the industry in South Africa. Feeding preferences of the sea urchin Tripneustes gratilla were tested by two different methods; a touch-preference test and a 48-hour consumption test. A touchpreference is established when the sea urchins' lantern teeth touched an algal species. The 48-hour consumption test was performed with paired combinations using four species of fresh algae. It was hypothesized that the preferred species would be similar in the touch-preference test and the consumption test. Five algal species were used in the touch-preference test; namely, Ecklonia maxima (kelp), Gigartina polycarpa, Grateloupia capensi, Porphyra capensis, and U/va rigida. Four of these species were used in the paired consumption test; namely, E. maxima, G. polycarpa, P. capensis and U. rigida. We found that E. maxima was most preferred in the touch-test followed by P. capensis and U. rigida. This result did not correlate with our consumption test. Here, U. rigida was significantly most preferred followed by E. maxima. Overall, the result is significant in relation to the prospect of echinoculture in South Africa as Ulva may provide a valuable alternate feed or supplement to this new industry. Due to the increase in time provided for the paired consumption test, we found that the paired consumption test was more conclusive in providing a preference for Tripneustes gratilla. Our results agree with literature which suggests that Tripneustes gratilla is a genera list feeder; however, Tripneustes gratilla shows definite preferences. Ulva spp. has been grown on a number of abalone farms in South Africa. Integrated aquaculture using T. gratilla and U. rigida as a biofilter and alternate feed is a very promising idea for echinoculture in South Africa.